Studi Kestabilan Tekanan Darah Pada Penderita Hipertensi Dan Faktor Yang Memengaruhinya - khasanah, suci; Irma Susanti, Maria Paulina (Viva Medika, 2019)
Instability of blood pressure is a condition in which the blood pressure is within the range of changes that tends to be constant. The blood pressure on the hypertensive people may change anytime, and it is difficult to be predicted. Even in some cases, the change of blood pressure cannot be felt by the sufferers, although it is much higher than the normal range. This may endanger the sufferers’ condition. This research aimed to know the blood pressure stability and the related factors of hypertensive people in Tambaksogra Village, Community Health Center 1 Sumbang. This research used observational analysis study design with cross sectional approach. The number of samples was 42 respondents; it was taken by using cluster sampling technique. The observation of blood pressure were done in 6 (six) days with daily measurement of the influencing factors. The data was analyzed by using lamda and coefficient of contingency. The result of the research showed that 90,5% of the respondents had unstable blood pressure (90,5%). The respondents with bad sleep quality were the most respondents who had unstable blood pressure (80,9%), p value 0,032; dominantly the respondents having unstable blood pressure were those who had normal level of stress (40,5%), p value 0,143; the obese respondents or non-obese respondents were the most respondents who had unstable blood pressure with p value 0,898. It can be concluded that almost all respondents have unstable blood pressure in six days observation and there is a correlation between sleep quality and the instability of blood pressure. Keywords: Blood Pressure Stability, Sleep Quality, Stress, and Obesity